Tarea 1

Ejercicio 10
Reducción de un término que contenga términos semejantes de diversas clases
1

7a − 9b + 6a − 4b =

2

a + b − c − b − c + 2c − a =

3

5 x − 11 y − 9 + 20 x − 1 − y =

4

− 6m + 8n + 5 − m − n − 6m − 11 =

5

− a + b + 2b − 2c + 3a + 2c − 3b =

6

− 81x + 19 y − 30 z + 6 y + 80 x + x − 25 y =

7

15a 2 − 6ab − 8a 2 + 20 − 5ab − 31 + a 2 − ab =

8

− 3a + 4b − 6a + 81b − 114b + 31a − a − b =

9

− 71a 3b − 84a 4 b 2 + 50a 3b + 84a 4b 2 − 45a 3b + 18a 3b =

10

− a + b − c + 8 + 2a + 2b − 19 − 2c − 3a − 3 − 3b + 3c =

11

m 2 + 71mn − 14m 2 − 65mn + m 3 − m 2 − 115m 2 + 6m 3 =

12

x 4 y − x 3 y 2 + x 2 y − 8 x 4 y − x 2 y − 10 + x 3 y 2 − 7 x 3 y 2 − 9 + 21x 4 y − y 3 + 50 =

13

5a x+1 − 3b x + 2 − 8c x +3 − 5a x+1 − 50 + 4b x + 2 − 65 − b x+ 2 + 90 + c x +3 + 7c x+3 =

14

a m+ 2 − x m +3 − 5 + 8 − 3a m+ 2 + 5 x m +3 − 6 + a m + 2 − 5 x m +3 =

15

0.3a + 0.4b + 0.5c − 0.6a − 0.7b − 0.9c + 3a − 3b − 3c =

16

1
1
3
1
3 1
a + b + 2a − 3b − a − b + − =
2
3
4
6
4 2

17

3 2
1
1
m − 2mn + m 2 − mn + 2mn − 2m 2 =
5
10
3

18

3
1
5
1
3
1
1
− a 2 + ab − b 2 + 2 a 2 − ab + b 2 − b 2 − 2ab =
4
2
6
3
4
6
3

19

3
2
1
0.4 x 2 y + 31 + xy 2 − 0.6 y 3 − x 2 y − 0.2 xy 2 + y 3 − 6 =
8
5
4

20

3 m−1 7 m− 2 3 m−1 1 m− 2
1
a − b + a − b − 0.2a m−1 + b m− 2 =
25
50
5
25
5

RESPUESTAS
1

7a − 9b + 6a − 4b
(7a + 6a ) = 13a

(− 9b − 4b ) = −13b

= 13a − 13b
2

a + b − c − b − c + 2c − a
a−a =0
b−b =0

− c − c + 2c = 0

=0
3

4

5 x − 11 y − 9 + 20 x − 1 − y
5 x + 20 x = 25 x
− 11 y − y = −12 y
= 25 x − 12 y − 10

− 9 − 1 = −10

− 6m + 8n + 5 − m − n − 6m − 11
− 6m − m − 6m = −13m
8n − n = 7 n

5 − 11 = −6

= −13m + 7 n − 6
5

− a + b + 2b − 2c + 3a + 2c − 3b
− a + 3a = 2a
b + 2b − 3b = 0

− 2 c + 2c = 0

= 2a
6

7

− 81x + 19 y − 30 z + 6 y + 80 x + x − 25 y
− 81x + 80 x + x = 0
19 y + 6 y − 25 y = 0
= −30 z

− 30 z

15a 2 − 6ab − 8a 2 + 20 − 5ab − 31 + a 2 − ab
15a 2 − 8a 2 + a 2 = 8a 2
− 6ab − 5ab − ab = −12ab

20 − 31 = −11

= 8a − 12ab − 11
2

8

− 3a + 4b − 6a + 81b − 114b + 31a − a − b
− 3a − 6a + 31a − a = 21a
4b + 81b − 114b − b = −30b

= 21a − 30b
9

− 71a 3b − 84a 4b 2 + 50a 3b + 84a 4b 2 − 45a 3b + 18a 3b
− 71a 3b + 50a 3b − 45a 3b + 18a 3b = −48a 3b
− 84a 4b 2 + 84a 4b 2 = 0
= −48a 3b

10

− a + b − c + 8 + 2a + 2b − 19 − 2c − 3a − 3 − 3b + 3c
− a + 2a − 3a = −2a
b + 2b − 3b = 0
− c − 2c + 3c = 0

+ 8 − 19 − 3 = −14

= −2a − 14
11

m 2 + 71mn − 14m 2 − 65mn + m3 − m 2 − 115m 2 + 6m3
m3 + 6m3 = 7 m3
m 2 − 14m 2 − m 2 − 115m 2 = −129m 2
= 7 m3 − 129m 2 + 6mn

71mn − 65mn = 6mn

12

x 4 y − x 3 y 2 + x 2 y − 8 x 4 y − x 2 y − 10 + x 3 y 2 − 7 x 3 y 2 − 9 + 21x 4 y − y 3 + 50

x 4 y − 8 x 4 y + 21x 4 y = 14 x 4 y
x2 y − x2 y = 0

− y3

− x 3 y 2 + x 3 y 2 − 7 x 3 y 2 = −7 x 3 y 2
− 10 − 9 + 50 = 31

= 14 x 4 y − 7 x 3 y 2 − y 3 + 31
13

5a x +1 − 3b x + 2 − 8c x + 3 − 5a x +1 − 50 + 4b x + 2 − 65 − b x + 2 + 90 + c x + 3 + 7c x + 3
5a x +1 − 5a x +1 = 0
− 3b x + 2 + 4b x + 2 − b x + 2 = 0
− 8c x + 3 + c x + 3 + 7c x + 3 = 0
= −25

14

− 50 − 65 + 90 = −25

a m + 2 − x m + 3 − 5 + 8 − 3a m + 2 + 5 x m + 3 − 6 + a m + 2 − 5 x m + 3
− x m +3 + 5x m +3 − 5 x m+ 3 = − x m +3
a m + 2 − 3a m + 2 + a m + 2 = − a m + 2

− 5 + 8 − 6 = −3

= −a m + 2 − x m +3 − 3
15

0.3a + 0.4b + 0.5c − 0.6a − 0.7b − 0.9c + 3a − 3b − 3c
0.3a + −0.6a + 3a = 2.7 a
0.4b − 0.7b − 3b = −3.3b

0.5c − 0.9c − 3c = −3.4c

= 2.7a − 3.3b − 3.4c
16

17

18

1
1
3
1
3 1
a + b + 2a − 3b − a − b + −
2
3
4
6
4 2
1
3
2+8−3
7
1
1
2 − 18 − 1
17
a + 2a − a =
a= a
b − 3b − b =
b=− b
2
4
4
4
3
6
6
6
7
17
1
= a− b+
4
6
4
3 2
1
1
m − 2mn + m 2 − mn + 2mn − 2m 2
5
10
3
3 2 1 2
6 + 1 − 20 2
13
m + m − 2m 2 =
m = − m2
5
10
10
10
13
1
= − m 2 − mn
10
3

3 1 3−2 1
− =
=
4 2
4
4

− 6 −1+ 6
1
1
mn = − mn
− 2mn − mn + 2mn =
3
3
3

3
1
5
1
3
1
1
− a 2 + ab − b 2 + 2 a 2 − ab + b 2 − b 2 − 2ab
4
2
6
3
4
6
3
3
− 9 + 28 2 19 2
1
1
3
2−3−8
9
a = a
ab − ab − 2ab =
ab = − ab
− a2 + 2 a2 =
4
3
12
12
2
4
4
4
− 5 +1− 2 2
5
1
1
6
− b2 + b2 − b2 =
b = − b 2 = −b 2
6
6
3
6
6
19
9
= a 2 − ab − b 2
12
4

19

20

3
2
1
0.4 x 2 y + 31 + xy 2 − 0.6 y 3 − x 2 y − 0.2 xy 2 + y 3 − 6
8
5
4
2
2−2 2
3 2
3 − 1.6 2 1.4 2
0.4 x 2 y − x 2 y =
x y=0
xy − 0.2 xy 2 =
xy =
xy = 0.175 xy 2
5
5
8
8
8
− 2.4 + 1 3 − 1.4 3
1
− 0.6 y 3 + y 3 =
y =
y = −.035 y 3
31 − 6 = 25
4
4
4
= 0.175 xy 2 − .035 y 3 + 25
3 m−1 7 m− 2 3 m−1 1 m− 2
1
a − b + a − b − 0.2a m−1 + b m− 2 =
25
50
5
25
5
3 m −1 3 m −1
3 + 15 − 5 m −1 13 m −1
a + a − 0.2a m −1 =
a =
a
25
5
25
25
− 7 − 2 + 10 m − 2 1 m − 2
7
1
1
b
− b m −2 − bm − 2 + bm −2 =
= b
50
25
5
50
50
13
1
= a m −1 + b m − 2
25
50

Sign up to vote on this title
UsefulNot useful